A mobile environmental air quality information system as a support for m-health - Mitreska, Elena; Davchev, Dancho; Mitreski, Kosta (Springer, Cham, 2013)
Considering mobile device limitations, such as storage, computing power and bandwidth, we propose a mobile cloud computing in order to provide the necessary resources and for delivery of any multimedia data like maps, alarms or messages to the mobile user devices. The main contribution of this paper is the scalability of our mCloud-based pollution monitoring system. The system can be extended to the entire territory of the country and it integrates all sensor pollution data with patient databases. By using mobile technologies, users/patients receive alerts concerning the air quality levels through user-friendly messages.
Keywords: Air Quality Index, Cloud Computing, m-Health, Lung Disease, Prevention, Alerts